(untitled) (Historia, 2021)
English This article traces the origins and development of Zimbabwe’s textile industry from the early colonial period to 1965, highlighting the role of the British Cotton Growing Association (BCGA) and the Empire Cotton Growing Corporation (ECGC) in helping to establish and promote, first, cotton-growing and, subsequently, the textile manufacturing industry in the country. It analyses the role and impact of the Cotton Research Industry Board (CRIB) from its establishment in 1936 and how, through its efforts, the country’s textile industry blossomed in the post-Second World War years, particularly following the signing of the 1948 Customs Agreement between Southern Rhodesia and South Africa and, how, for a variety of reasons, including growing regional political uncertainty, the textile manufacturing industry went into relative decline. As a result, attempts by the government in 1958 to sell its cotton-spinning mills established under the auspices of the CRIB in the town of Gatooma, met lukewarm responses from potential buyers. It was only eighteen months later that the government was able to sell the mills to a British company, David Whitehead Limited, at an almost give-away price. By the end of the Federation and with Rhodesia’s Unilateral Declaration of Independence looming, therefore, the future of the textile manufacturing industry appeared uncertain. The article hopes to encourage further research into the fortunes of the textile industry in the UDI period and beyond, in order to deepen understanding of the role and fate of this sector after Zimbabwe’s independence. Afrikaans Gedeeltelik Beskerm: Die Oorsprong en Groei van Koloniale Zimbabwe se Tekstielbedryf, 1890-1965 Hierdie artikel ondersoek die oorsprong en ontwikkeling van Zimbabwe se tekstielbedryf van die vroeë koloniale periode tot 1965, met klem op die rol wat die British Cotton Growing Association en die Empire Cotton Growing Corporation gespeel het in die totstandkoming en bevordering van katoenverbouing en die tekstielvervaardigingsbedryf in die land. Die rol en invloed van die Cotton Research Industry Board (CRIB) sedert die ontstaan daarvan in 1936 word geanaliseer, asook hoe die land se tekstielbedryf deur dié organisasie se insette in die jare na die Tweede Wêreldoorlog gedy het, veral nadat die Doeane Ooreenkoms van 1948 tussen Suid-Rhodesië en Suid-Afrika onderteken is. Dit ondersoek ook hoe dié bedryf om verskeie redes, insluitend die toenemende politiese onsekerheid in die streek, begin agteruitgaan het. Gevolglik is pogings van die Staat in 1958 om sy katoenspinmeule (wat onder die leiding van die CRIB in Gatooma tot stand gebring is) van die hand te sit, met louwarm belangstelling deur potensiële kopers begroet. Eers agtien maande later het die Staat die meule teen ŉ bykans weggee-prys aan ŉ Britse maatskappy, David Whitehead Limited, verkoop. Teen die einde van die Federasie en op die vooraand van Rhodesië se Eensydige Onafhanklikheidsverklaring, het die toekoms van die tekstielvervaardigingsbedryf dus onseker gelyk. Hierdie artikel hoop om verdere navorsing oor die wel en weë van dié bedryf tydens die EOV-tydperk en daarna te stimuleer, ten einde insig in die rol en lotgevalle van dié sektor na Zimbabwe se onafhanklikheidswording te bevorder.